Sample loading and retrieval by centrifugation in a closed-loop PCR microchip - Lok, Khoi Seng (2012)
We report on a novel concept of sample loading for microfluidic devices using a benchtop centrifuge and a magnetically actuated circular closed-loop PCR microchip as a model system. The PCR mixture and the ferrofluid were loaded into a specially designed microchip. The microchip was then placed in an off-the-shelf 50-mL tube and centrifuged. The strong centrifugal force drives the PCR mixture and the ferrofluid into the microchannels of the microchip, and simultaneously expels any trapped microbubbles. PCR was successfully carried out on single and parallel closed-loop PCR microchips. The addition of a few off-chip handling steps allows great simplification of the device design. This new loading concept may be useful for designing robust and low-cost lab-on-a-chip devices because benchtop centrifuges are quite common in most laboratories.